Accelerated T2 mapping combining parallel MRI and model‐based reconstruction: GRAPPATINI. Issue 2 (15th February 2018) - Hilbert, Tom; Sumpf, Tilman J.; Weiland, Elisabeth; Frahm, Jens; Thiran, Jean‐Philippe; Meuli, Reto; Kober, Tobias; Krueger, Gunnar
Abstract : Background: Quantitative T2 measurements are sensitive to intra‐ and extracellular water accumulation and myelin loss. Therefore, quantitative T2 promises to be a good biomarker of disease. However, T2 measurements require long acquisition times. Purpose: To accelerate T2 quantification and subsequent generation of synthetic T2 ‐weighted (T2 ‐w) image contrast for clinical research and routine. To that end, a recently developed model‐based approach for rapid T2 and M0 quantification (MARTINI) based on undersampling k ‐space, was extended by parallel imaging (GRAPPA) to enable high‐resolution T2 mapping with access to T2 ‐w images in less than 2 minutes acquisition time for the entire brain. Study Type: Prospective cross‐sectional study. Subjects/Phantom: Fourteen healthy subjects and a multipurpose phantom. Field Strength/Sequence: Carr–Purcell–Meiboom‐Gill sequence at a 3T scanner. Assessment: The accuracy and reproducibility of the accelerated T2 quantification was assessed. Validations comprised MRI studies on a phantom as well as the brain, knee, prostate, and liver from healthy volunteers. Synthetic T2 ‐w images were generated from computed T2 and M0 maps and compared to conventional fast spin‐echo (SE) images. Statistical Tests: Root mean square distance (RMSD) to the reference method and region of interest analysis. Results: The combination of MARTINI and GRAPPA (GRAPPATINI) lead to a 10‐fold accelerated T2 mapping protocol with 1:44 minutes acquisition time and full brain coverage. The RMSD of GRAPPATINI increases less (4.3%) than a 10‐fold MARTINI reconstruction (37.6%) in comparison to the reference. Reproducibility tests showed low standard deviation (SD) of T2 values in regions of interest between scan and rescan (<0.4 msec) and across subjects (<4 msec). Data Conclusion: GRAPPATINI provides highly reproducible and fast whole‐brain T2 maps and arbitrary synthetic T2 ‐w images in clinically compatible acquisition times of less than 2 minutes. These abilities are expected to support more widespread clinical applications of quantitative T2 mapping. Level of Evidence: 2 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2018;48:359–368.